Evidence for an Oceanic Source of Methyl Ethyl Ketone to the Atmosphere. Issue 4 (25th February 2020) - Brewer, J. F.; Fischer, E. V.; Commane, R.; Wofsy, S. C.; Daube, B.C.; Apel, E. C.; Hills, A. J.; Hornbrook, R. S.; Barletta, B.; Meinardi, S.; Blake, D. R.; Ray, E. A.; et al.
Abstract: Methyl ethyl ketone (MEK) is a relatively abundant but understudied oxygenated volatile organic compound that can serve as a source of both HOx and PAN when photooxidized. We use aircraft observations of MEK from the remote marine troposphere to show that the ocean serves as a source of MEK to the atmosphere during both meteorological winter and summer. There is pronounced seasonality in the MEK profiles in the extratropical troposphere, with higher MEK mixing ratios observed in summer than in winter. MEK in clean air over the remote oceans correlates with both acetone and acetaldehyde, whose primary sources in the ocean water are the photooxidation of organic material. We show that even a small (>1 nM) concentration of MEK in surface waters is sufficient to allow the ocean to be a net source of MEK to the atmosphere over ocean basins across multiple seasons. Plain language summary: Methyl ethyl ketone (MEK) is an abundant but understudied gas in Earth' atmosphere, which is emitted into the atmosphere from both human and natural sources. When MEK is broken apart by ultraviolet sunlight, the products released by those reactions play important roles in the formation and destruction of air pollution. In this paper, we show that the oceans are a source of MEK to the atmosphere. The oceanic emissions we document correlate strongly with some other gases that are known to be produced in the ocean but not those most closely associated with the growth of microscopic oceanic phytoplankton. Finding this new source helps us better understand the importance of MEK to the atmosphere and provides guidance for future oceanic and atmospheric research. Key Points: We use aircraft observations of MEK from the remote marine troposphere to suggest that the ocean is a source of MEK to the atmosphere Evidence exists for this source in both winter and summer in the tropical Pacific, south Atlantic and Pacific, and in the Southern Ocean MEK in clean air over the remote oceans does not correlate with DMS, but it does correlate with acetone and acetaldehyde